Chronic Hepatitis C: An Overview of Evidence on Epidemiology and Management from a Brazilian Perspective - Rodolfo Castro; Hugo Perazzo; Beatriz Grinsztejn; Valdilea G. Veloso; Chris Hyde (International Journal of Hepatology)
Chronic hepatitis C remains one of the main causes of chronic liver disease worldwide and presents a variable natural history ranging from minimal changes to advanced fibrosis and cirrhosis and its complications, such as development of hepatocellular carcinoma. Approximately, 1.45 million people are estimated to be infected by HCV in Brazil representing a major public health issue. The aim of this paper was to review the epidemiology and management of chronic hepatitis C from a Brazilian perspective. The management of chronic hepatitis C has been challenged by the use of noninvasive methods to stage liver fibrosis as an alternative to liver biopsy and the high cost of new interferon-free antiviral treatments. Moreover, the need of cost-effectiveness analysis in hepatitis C and the recent changes in treatment protocols were discussed.